Assessing the Environmental Impact of Textiles and the Clothing Supply Chain - Muthu, Subramanian Senthilkannan, author 576529; ScienceDirect (Online service) 7722 (Cambridge : Woodhead Publishing, 2020)
Assessing the Environmental Impact of Textiles and the Clothing Supply Chain, Second Edition, is a fully updated, practical guide on how to identify and respond to environmental challenges across the supply chain. This new edition features updates to important data on environmental impacts and their measurements, the sustainable use of water and electricity, and new legislation, standards and schemes. Chapters provide an introduction to the textile supply chain and an overview of the methods used to measure environmental impacts, including greenhouse gas emissions, water and energy footprints, and a lifecycle assessment (LCA) on environmental impacts. This book will be a standard reference for R&D managers in the textile industry and academic researchers in textile science.